FERTILITY PATTERNS AND MATERNAL CHARACTERISTICS ACROSS NIGERIA'S GEOPOLITICAL ZONES: A LONGITUDINAL STUDY FROM 2003 TO 2018: A Longitudinal Study from 2003 to 2018 - Mashood, Lawal Olumuyiwa; Elemosho, Mubarak; Abubakar, Ibrahim Dangani (FUDMA JOURNAL OF SCIENCES, 2024)
This study examines the reproductive and demographic traits of mothers in Nigeria while utilizing secondary data from the Nigeria Demographic and Health Survey (NDHS). The study uses Structural Equation Modeling (SEM) to examine the relationship between socioeconomic status, reproductive behaviour, and geo-cultural factors affecting fertility patterns in Nigeria. The results show that the average age of mothers at first birth has gradually increased, while the proportion of mothers with no formal education remains significant. The model reveals significant insights into how these latent constructs interact. The model indicates that higher SES leads to fewer children, while reproductive behaviours like age at first birth and marital status positively influence the total number of children ever born. The model fit indices: RMSEA of 0.072; TLI of 0.903; and CFI of 0.947, demonstrate a reasonable fit, suggesting that the model adequately captures the underlying relationships, but some coefficients suggest measurement issues. The study emphasizes the importance of cultural norms and socioeconomic conditions in shaping reproductive choices.
Keywords: Fertility patterns; Structural equation model; Socioeconomic status; Reproductive behavior; Demographic traits; Model fit indices